4‐Fluorobenzylpiperazine‐Containing Derivatives as Efficient Inhibitors of Mushroom Tyrosinase. (20th August 2020) - Vittorio, Serena; Ielo, Laura; Mirabile, Salvatore; Gitto, Rosaria; Fais, Antonella; Floris, Sonia; Rapisarda, Antonio; Germanò, Maria Paola; De Luca, Laura
Abstract: Tyrosinase is a type‐3 copper protein involved in the biosynthesis of melanin pigments; therefore, the inhibition of its enzymatic activity represents a promising strategy for the treatment of hyperpigmentation‐related disorders. To address this point, we previously designed a class of 4‐(4‐fluorobenzyl)piperazin‐1‐yl‐based compounds, which proved to be more active inhibitors against tyrosinase from mushroom Agaricus bisporus than the positive control kojic acid. Herein, we report the synthesis of further series of 4‐(4‐fluorobenzyl)piperazin‐1‐yl analogues bearing a (hetero)aromatic fragment as key feature to improve protein affinity. The newly synthesized compounds were assayed in vitro and proved to be potent inhibitors in the low‐micromolar range. The active 2‐thienyl and 2‐furyl derivatives were selected for further modification to allow their binding mode to be analyzed by docking studies and to give satisfactory safety profiles. Abstract : Melanin mitigation : We report the design and synthesis of a new series of tyrosinase inhibitors with a 4‐fluorobenzylpiperazine scaffold. The obtained compounds were tested to evaluate their ability to inhibit mushroom tyrosinase. The cytotoxicity was also evaluated for selected derivatives, and docking studies were conducted to investigate their binding mode within the tyrosinase catalytic pocket.